Combating Corruption in Indonesia : Enhancing Accountability for Development - World Bank (Washington, DC, 2013)
Given steady progress in the development of democracy - establishment of effective checks on arbitrary rulers, replacement of arbitrary rules with just and honest ones, and, participation of ordinary people in the making of rules - Indonesia could over time, emerge as a strong functioning democracy. Yet, continued progress towards a full-fledged democracy cannot be taken for granted, precisely because the transition to an elected government has been a largely peaceful one, indeed allowed the powerful interests that dominated the New Order-the former First Family, the military, and the conglomerates-to continue to operate, and indeed flourish in this new environment. It is in this context the problem of corruption in Indonesia must be viewed. This report is an initial outcome of an ongoing process of rethinking, and learning by the Bank, on issues of accountability, and corruption in Indonesia. In the aftermath of the financial crisis, and related political upheaval, the Bank revisited its entire strategy towards the country. The report builds on a comprehensive set of diagnostic assessments, and reviews on some of the main areas where corruption breeds: public expenditure and financial management systems, procurement, inter-governmental fiscal relations, the financial sector, forestry and infrastructure, the justice sector, and the civil service. It also attempts to distill from studies the key lessons learnt about corruption, and accountability, and, to better understand how corruption works in particular sectors, and processes. The central issue examined in this report is why public accountability fails so often, and, after analyzing the context in which anti-corruption efforts must operate in Indonesia, the report focuses first on three areas of corruption: the budget, local governments and the government's regulatory functions in selected sectors - banking, electricity and forestry. It then looks at the justice sector - the police, the prosecutors, the courts and the Indonesian civil service. Finally, it analyzes how donors are responding to the challenge of corruption, drawing primarily on the Bank's own experience.